ORGANIZATION OF STUDENT-CENTERED TRAINING IN THE SYSTEM OF ADDITIONAL EDUCATION OF ADULTS - Nevdakh, Svetlana (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2019)
The article presents one of the modern trends in the development of the education system - the organization of student-centered training. Extrapolation of this type of training into the system of additional education of adults will allow to prepare a specialist with modern thinking, focused on innovation, continuous self-development. The purpose of the research is to explore the possibilities of implementing student-centered training tools into the practice of realization retraining programs for educational specialists. Research methods: a theoretical analysis of the essence of the concept of “student-centered training”, analysis of the characteristics of adult education, experimental work on testing methods of student-centered training in the system of additional education of adults. The main results of the research: methods of student-centered training of adults have been adapted to the specifics of organizing retraining programs, conditions for organizing student-centered training in institutions of additional education of adults have been identified, methodical recommendations have been developed. The use of these recommendations will optimize the implementation of retraining programs for education specialists.